Risk and boundary work in contemporary maternity care: tensions and consequences - Spendlove, Zoey (Taylor & Francis, 2018)
While the organisation of work in maternity care has historically witnessed boundary work between midwives and obstetricians, modern service provision has posed many challenges to professional boundary work, with increasing litigation and risk management practices fuelling the social construction of a ‘risk discourse’ within maternity care. Drawing upon observational and interview data of an ethnographic study conducted in a UK obstetric-led maternity unit during 2013, this article explores the professional experiences of contemporary ‘risk work’ and the impact of such ‘risk work’ upon the professional role boundaries of obstetricians and midwives. Midwives and obstetricians expressed concern regarding risk in childbirth. Obstetricians and midwives perceived control over the childbirth process as a means of promoting risk minimisation, so that risk management was central to the perceived rational management of uncertainty in maternity care. Anxiety over uncertainty, error and blame was associated with dominance of the biomedical model of care in translating and managing risk and a perceived increase in the medicalisation of childbirth. Such ‘risk discourse’ had consequently provoked boundary work tension, with the perceived shifting of professional role boundaries of obstetricians and midwives within maternity care. As a consequence of contemporary risk work and reconfiguration of role boundaries, the role of the midwife in the twenty-first century was perceived to be in a state of flux. I note that contemporary risk work and the reconfiguration of professional boundaries in maternity services potentially places the midwifery profession ‘at risk’ of deprofessionalisation, raising concerns for the future role and professional status of midwives.